(untitled) (Bangladesh Pharmaceutical Journal, 2025)
There has been a recent increase in interest in exploring marine microorganisms and fauna as sources of bioactive metabolites for biotechnological applications. This study adds to the field by exploring an antagonistic microorganism isolated from the Sundarbans mangrove forest in Bangladesh, identified as a Streptomyces sp. based on its morphological features. The bacterial isolates were grown in a yeast extract-glucose liquid medium for seven days at 37.5°C in order to stimulate the production of bioactive metabolites. The culture filtrate was subsequently extracted with chloroform and ethyl acetate. The ethyl acetate extract (200 μg/disc) shown antibacterial activity against gram-positive and gram-negative bacteria, including Bacillus subtilis and Escherichia coli, with inhibition zones of 28 mm and 27 mm, respectively. The chloroform extract produced smaller zones of 25 mm and 27 mm. Both extracts demonstrated promising antibacterial activity compared to Kanamycin (30 μg/disc). The brine shrimp lethality test demonstrated strong cytotoxic action, with the chloroform extract exhibiting the highest potency (LC50=2.2 μg/ml) and the ethyl acetate extract demonstrating an LC50 of 0.9 μg/ml. Cephalosporin served as a positive control with an LC50 of 1.6 μg/ml. These findings demonstrate the extracts potential as bioactive chemicals with cytotoxic characteristics. Bangladesh Pharmaceutical Journal 28(2): 135-141, 2025 (July)